Affective neurolinguistics: a new field to grow at the intersection of emotion and language? – Commentary on Hinojosa et al., 2019. Issue 7 (3rd September 2020) - Kissler, Johanna
ABSTRACT: This paper comments on the recently proposed research framework of "affective neurolinguistics" and discusses it in relation to various theories of emotion and domains of language processing. In line with Hinojosa, Moreno, and Ferré [2019. Affective neurolinguistics: Towards a framework for reconciling language and emotion. Language, Cognition and Neuroscience, 0(0), 1–27], the potential of "affective neurolinguistics" in the lexico-semantic and morphosyntactic domains is acknowledged. Going beyond that, the claim is made that to fully appreciate the importance of affect in language processing and to unify and bring out the full potential of this field, the theoretical framework should be context-sensitive and adopt a genuine communicative perspective from the start.